(untitled) (Revista Contexto & Saúde, 2022)
To document the care on the patient is a necessary skill to the pharmacist. The goal of the study is to prepare educational tutorials related to the registration of Clinical Pharmacy activities in the medical record. It is a technological production carried out in two stages: quantitative cross-sectional study and preparation of educational tutorial videos. Data collection occurred through an online survey of pharmacists active in Brazilian hospitals and Pharmacy professors. The preparation of the educational tutorial videos followed the ADDIE model. 47 professors participated in the research, 100% consider the theme important; and 80% believe that the undergraduate program does not prepare the student for the recording in the medical records. Among the 248 participating pharmacists: only 9% received guidance on the subject during undergraduate course; and less than 40% felt able to record clinical activities in medical records. Three tutorial videos on the recording of the pharmacist’s in the medical records were made. The research indicated a need to update the knowledge of Brazilian pharmacists related to the theme record in medical records in services and teaching. The three tutorial videos on the registration of the pharmacist in the medical records were elaborated to disseminate knowledge to pharmacists.